Jak zmierzyć demokrację? Skale pomiaru demokracji politycznej stosowane w politologii porównawczej - SZEWCZAK, Wiktor (Przegląd Politologiczny, 2018)
The author reviews and characterizes the most important scales for measuring the democracy of political systems, applied in Western, mainly Anglo-Saxon, comparative political science. He refers to his article published in a back issue of Przegl¹d Polityczny, where the fundamental theoretical and methodological issues of democracy measuring were presented, and tries to indicate how these issues are dealt with by various researchers whose scales and data bases are most common and most frequently referred to in research into political comparative studies. The paper describes S. Huntington’s analyses, the Freedom House scale, the IDEA assessment of the quality of democracy, the EIU democracy index, Bollen’s scale, the Political Regimes Project, the Polity Project, T. Vanhanen’s democracy index and the scale of polyarchy by Coppedge and Reinicke. As the author analyzes one scale and database after another, he tries to identify their strengths and weaknesses, determine the most characteristic properties of each proposal, and assess their applicability in comparative analyses, pointing to their potential benefits and the threats of using them. In conclusion, he recommends caution in the selection of a scale to become a foundation for potential analyses, while he acknowledges that this theoretical and methodological tool is highly useful.